Trade in Business Services Within the Visegrad Countries - Ambroziak, Adam A.; Stefaniak, Joanna (Publishing House of Wroclaw University of Economics and Business, 2025)
Business services, with their important impact on sustainable development, are becoming increasingly important in international trade. As the countries of the Visegrad Group (V4) are expected to cooperate closely within the European Union, the authors assume that this should also be reflected in their trade in business services. The aim of this paper was to determine the trade position of the V4 countries in mutual business services trade compared to other EU Member States (EU-23) in the period 2014-2023. To this end, the study compared the trade positions as determined by the Trade Balance Index and the Revealed Symmetric Comparative Advantage indicator. Given the diversity of business services, selected sectors were evaluated, including ICT, RDI, accounting, consulting, architectural and engineering services. The results confirm that closer cooperation in mutual trade is evident for individual V4 countries. While trade positions vary by service type, they are generally stronger in mutual trade than with the EU-23. However, in terms of trade with the EU-23, the trade positions of the V4 remain generally weaker than those of the other EU countries.
Quote as: Ambroziak, A. A., & Stefaniak, J. (2025). Trade in Business Services Within the Visegrad Countries. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives (pp. 75-90). Publishing House of Wroclaw University of Economics and Business.
Keywords: trade; business services; Visegrad Countries